Prevalence and Trends in Low Bone Density, Osteopenia and Osteoporosis in U.S. Adults With Non-Alcoholic Fatty Liver Disease, 2005–2014 - Zhai, Tianyu; Chen, Qi; Xu, Jing; Jia, Xi; Xia, Pu (Frontiers in Endocrinology, 2022)
Abstract Background & Aims: Non-alcoholic fatty liver disease (NAFLD) is suggested to be associated with bone mineral density (BMD) alterations; however, this has not been ascertained. The current study aimed to investigate the changes in BMD and the prevalence of osteopenia/osteoporosis in US adults with or without NAFLD and to evaluate their association. Methods: The study was conducted based on data collected from the U.S. National Health and Nutrition Examination Survey (NHANES) during the period 2005–2014. A total of 13 837 and 6 177 participants aged > 20 years were eligible for conducting the Hepatic Steatosis Index (HSI) and the US Fatty Liver Index (USFLI) analysis, respectively. Results: From 2005–2014, a downward trend in femoral neck BMD was observed in subjects with NAFLD aged ≥ 40. After adjustment for potential confounders, an upward shift occurred in the prevalence of osteopenia/osteoporosis at the femoral neck in adults aged ≥ 40, particularly in women ≥ 60 years old and men below the age of 60. Moreover, a negative association was found between BMD and NAFLD markers (USFLI, HSI), whereas NAFLD with advanced fibrosis was positively associated with the prevalence of spine fractures. Conclusions: There was a trend toward lower BMD and higher prevalence of osteopenia/osteoporosis at the femoral neck in US adults with NAFLD aged ≥ 40 years during the period of 2005–2014. NAFLD with advanced fibrosis was positively associated with a higher risk of spine fracture. More research is required to fully investigate the mechanism and consequence of poor bone health in NAFLD patients and consider optimum management of osteopenia/osteoporosis for this population.